Efektivitas Pembelajaran Berbasis Ethnomathematics Dengan Pendekatan Budaya Sasak Ditinjau Dari Pemahaman Konsep Matematika - Fauzi, Asri; Umar, Umar; Rahmatih, Aisa Nikmah (Pendagogia: Jurnal Pendidikan Dasar, 2023)
The aim of this research is to find out how effective ethnomathematics-based learning is with a Sasak cultural approach in terms of understanding mathematical concepts. This type of research is quasi-experimental research with a one group posttest only design. The sample for this research was 32 PGSD students at Mataram University. The data collection technique in this research is the test technique. Meanwhile, the instrument used to measure concept understanding is an objective test that includes elements of Sasak culture in the test questions. The data analysis technique uses the praysarat test, namely the normality test and hypothesis testing uses the t-test with the One-Sample T Test type. The research results show that the results of the one sample test with a proportion of students who passed was 75%, it was found that the significance value was 0.005. This means that the significance score is less than 0.05 so that a decision is made that ethnomathematics-based learning with a Sasak cultural approach is effective in terms of students' ability to understand concepts.